1981
DOI: 10.1007/bf02468840
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of rat liver viability enhanced by cold flushing with oxygenated perfluorochemicals

Abstract: The possible benefit of oxygenation during initial cold flushing was investigated as means of improving the quality of live preservation in rats. In five group of animals (total 61 experiments), the lives were flushed with different perfusates. Non-oxygenated groups included controls, Collins' solution alone and Collins' solution containing perfluorotributylamine (FC-43). In the oxygenated groups, Collins' solution alone and collins' solution containing FC-43 were oxygenated by bubbling. The hepatic ATP level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Dawkins et al [18] stated that an important factor contributing to cell death is loss of nucleotides, ATP, and that maintenance of adequate levels of ATP is essential for the preservation of liver cells. Konno et al [7] found no remarkable histo logical changes of the liver containing high ATP levels 8 h after preservation by flushing with cold modified Collins solution and high oxygenated perfusate. Watanabe et al [16] reported that a small amount of ATP was necessary for the initial step of its own repro duction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dawkins et al [18] stated that an important factor contributing to cell death is loss of nucleotides, ATP, and that maintenance of adequate levels of ATP is essential for the preservation of liver cells. Konno et al [7] found no remarkable histo logical changes of the liver containing high ATP levels 8 h after preservation by flushing with cold modified Collins solution and high oxygenated perfusate. Watanabe et al [16] reported that a small amount of ATP was necessary for the initial step of its own repro duction.…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in the cellular level of ATP dur ing anoxia is a common occurrence [6][7][8][9] due to cessation of oxidative phosphoryla tion, lack of oxygenation leading to restraint of the sodium-potassium pump, disappear ance of membrane potentiality and finally cell death [5,9,16,17]. Dawkins et al [18] stated that an important factor contributing to cell death is loss of nucleotides, ATP, and that maintenance of adequate levels of ATP is essential for the preservation of liver cells.…”
Section: Discussionmentioning
confidence: 99%